2012
DOI: 10.1002/jmv.23256
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hepatitis C virus infection in Inland Brazil: An analysis of pooled epidemiological sectional studies

Abstract: In order to assess the contribution of different parenteral routes as risk exposure to the hepatitis C virus (HCV), samples from nine surveys or cross-sectional studies conducted in two Brazilian inland regions were pooled, including a total of 3,910 subjects. Heterogeneity among the study results for different risk factors was tested and the results were shown to be homogeneous. Anti-HCV antibodies were observed in 241 individuals, of which 146 (3.7%, 95% CI = 3.2-4.4) had HCV exposure confirmed by immunoblot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…However, this contradicts results reported in a recent MA study done in Brazil. Souto and coworkers found no association between HCV infection and sexual activity and suggested, in agreement with Poynard et al ., 2003 that this exposure is not a very effective route to HCV spread .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this contradicts results reported in a recent MA study done in Brazil. Souto and coworkers found no association between HCV infection and sexual activity and suggested, in agreement with Poynard et al ., 2003 that this exposure is not a very effective route to HCV spread .…”
Section: Discussionmentioning
confidence: 99%
“…Tattooing has been considered by some epidemiologists to be a minor risk factor for HCV infection . Meanwhile, multivariate analysis showed conflicting results on this issue . Although prospective studies have shown some acupuncture risk factors to be relatively safe , numerous case reports revealing serious complications, including infection with hepatitis, continue to emerge in both industrialized and developing countries .…”
mentioning
confidence: 99%
“…Souto et al evaluated the contribution of different parenteral routes of exposure to hepatitis C, including samples from nine cross-sectional studies, with a total of 3,910 individuals, and confirmed the use of injectable drugs as the main risk factor for HCV 33 .…”
Section: Discussionmentioning
confidence: 98%
“…Varios estudios han tratado de evaluar si los tatuajes son un factor de riesgo para el contagio del virus de la hepatitis C (VHC) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). En Colombia solo existen 2 estudios sobre sus factores de riesgo.…”
Section: Introductionunclassified